'Having drunk heresy with their (mother's) milk': English Protestant converts to Catholicism in Malta, 1600–1798. Issue 2 (October 2022) - Ciappara, Frans
Abstract : This article analyses the conversion of 379 English Protestants to Catholicism in Malta between 1600 and 1798. It explores the motivations behind their recantation, the agents of their conversion and the role of dissimulation in discarding their Protestant faith. It ends with two remarks. First, people in the Mediterranean 'knew no religious frontiers'. 1 Malta, like other Mediterranean territories was a place with a mixed religious profile. Second, though English Protestants considered themselves to be the 'elect' and their country the new Israel, the two faiths were not mutually exclusive and could find common ground over the defence of Christendom.